2014
DOI: 10.1179/1743133614y.0000000123
|View full text |Cite
|
Sign up to set email alerts
|

Formation behaviour of blister in cast aluminium alloy

Abstract: The formation behaviour of a blister in a die cast aluminium alloy was observed by employing a combined methodology of in situ three-dimensional observation using X-ray microtomography and image based simulation. It has been revealed, via a reverse approach based on the simulation, that nitrogen and carbon dioxide gases fill the blister nucleus. Spontaneous growth of the blister nucleus occurs through creep deformation of the surrounding aluminium due to the blister nucleus' high internal gas pressure. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…2a). Closely spaced hydrogen micropores are prone to form larger pores through coalescence partly due to the superposition of hydrostatic strain fields among neighboring pores [22]. In contrast, almost no coalescence of neighboring hydrogen micropores is observed for those nucleated on the tips of Al 2 CuMg/Al 7 Cu 2 Fe particles, as shown on particle A in Fig.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…2a). Closely spaced hydrogen micropores are prone to form larger pores through coalescence partly due to the superposition of hydrostatic strain fields among neighboring pores [22]. In contrast, almost no coalescence of neighboring hydrogen micropores is observed for those nucleated on the tips of Al 2 CuMg/Al 7 Cu 2 Fe particles, as shown on particle A in Fig.…”
mentioning
confidence: 91%
“…where P is the internal gas pressure, γ is the surface tension of aluminum and d is the diameter of a pore. The internal gas pressure of a typical hydrogen micro pore (1 μm) is approximately 4 MPa under the assumption of γ = 1.16 N m -1 [22]. Therefore, it can be inferred that the growth of hydrogen micropores under high temperatures is induced by the creep deformation of the surrounding aluminum matrix caused by the high internal gas pressure [13,22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have shown that in hydrogenated metals, blisters usually grow with increasing temperature 14 23 24 25 . However, occasionally they could also shrink or disappear 26 27 .…”
mentioning
confidence: 98%
“…However, occasionally they could also shrink or disappear 26 27 . The accelerated blister growth is often interpreted as simply due to the rise of internal gas pressure in the hydrogen-filled cavities 24 25 , while the reason for shrinkage is still elusive. However, there are other important factors that can instigate and mediate blistering but have not been taken into consideration fully.…”
mentioning
confidence: 99%